Adsorption of humic acid fractions by a magnetic ion exchange resin. (2nd March 2022) - Ding, Lei; Wang, Dandan; Li, Ling; Jia, Yunhan; Ma, Jiangya; Wang, Feifei; van der Hoek, Jan Peter
Abstract: Natural organic matter in waters varies in different fractions. To better understand the removal of different fractions by a magnetic ion exchange (MIEX) resin and the mechanism behind it, this study investigated adsorption kinetics, equilibrium and thermodynamics of humic acid (HA) fractions with different hydrophilic–hydrophobic properties and molecular weights on MIEX resin through a series of batch experiments. MIEX resin can effectively remove approximately 40% of hydrophilic and 30% of hydrophobic HA components, as well as approximately 44% of molecular weight (MW) <10 kDa to some degree. The removal efficiency of HA fractions by MIEX resin reduced with the increase of pH from 6 to 9. Adsorption kinetics of different HA fractions on MIEX resin fitted the pseudo-second-order model well. With the increase of MW of HA from <1 kDa to >10 kDa, the time to reach adsorption equilibrium reduced from 180 to 120 min. It took more time for the hydrophilic fractions (140 min) to reach the equilibrium than for hydrophobic HA fractions (120 min). The Sips model fitted the adsorption equilibrium data of HA fractions on MIEX resin well. It was revealed that the adsorption of HA fractions on MIEX resin was spontaneous, endothermic and an entropy driven process, and the chemisorption might dominate the adsorption of HA components on MIEX resin. This study is of great significance to the design of magnetic ion exchange resin reactors and the optimization of operational parameters for the removal of natural organic matter with different hydrophilic–hydrophobic properties and molecular weights in different water sources. HIGHLIGHTS: MIEX resin can remove hydrophilic and hydrophobic HA and MW <10KDa HA. The removal of 8 HA fractions by MIEX resin decreases with pH increase. The equilibrium time is related to hydrophobicity and MW of HA. The equilibrium time decreases with the increase in MW of HA fractions. Kinetics and adsorption equilibrium models were established. Graphical Abstract